Institutional imbalances in the territorial development management model - Monastyrskyi, Grygorii; Volosiuk, Maryna (Herald of Economics, 2022)
Introduction. It is extremely important to improve the management of territorial development and to determine the priorities of state regional policy and to harmonize national, regional and local interests. At the present stage, the institutional support for the development of territories is characterized by the slowness of state measures to implement reforms, the inconsistency of regional and local development and «point» bills. Therefore, today there is an urgent need to explore the essence of institutional imbalances and their impact on the management of territorial development.Purpose of the research. Research of defining features of the development of territories, the characteristics of the evolutionary transformations of the state regional policy of Ukraine and the definition of institutional imbalances in the modern management model and their impact on the development of territories.Research methods. To achieve this goal, the following research methods were used: system analysis, systematization, generalization - to identify signs of development of territories; chronological - to study the peculiarities of the evolutionary transformations of the state regional policy of Ukraine; institutional analysis - to determine the impact of institutional imbalances on the development of territories.Results. The signs of the development of territories are highlighted, namely: the impact of the development of territories on the national economy as a whole; rational use of various territorial resources through effective institutional mechanisms and management tools; development is always associated with the spatial organization of the territory; the real development of territories is based on partnership relations between public authorities, business representatives and the public. The features of evolutionary transformations and the current state and specificity of the state regional policy of Ukraine are investigated: from smoothing disproportions in regional development and solving point chronic problems to socio-economic cohesion and unity of the country and sustainable growth in the quality of human life, regardless of where he was born, where he lives now and where he will live in the future. It has been proved that decentralization is primarily due to the declared state regional policy, which determines the scale and pace of reforms, and that the relationship between decentralization and the development of territories is ambiguous, since in the context of the new state regional policy, the problems of institutional support for managing the development of territories lead to a number of contradictions and imbalances. , namely: the formation of a hierarchical system of regional and local authorities has not been completed; low involvement of state authorities and local self-government bodies at the district and regional level in the processes of organizing cooperation between territorial communities; lack of a full-fledged system for monitoring the impact of reforms on the development of territories; inadequate participation in the territorial development management model of the Regional Development Agencies; the development of territories requires not only their effective functioning, but also ensuring economic security. It has been determined that the development of territories requires both the effectiveness of measures of state regional policy and the development of local authorities, since the decentralization reform itself will be perceived as an expansion of the powers of local authorities, and therefore the ability of local residents to develop, finance and implement local policy.Perspectives. In the conditions of realization of the new state regional policy the prospects of further scientific researches are directions of improvement of institutional maintenance of management of development of territories.